Production of aromatics from butanol over Ga-promoted HZSM5 catalysts: tuning of benzene–toluene–xylene and ethylbenzene (BTEX) selectivity. Issue 5 (22nd February 2022) - Kella, Tatinaidu; Shee, Debaprasad
Abstract : The present investigation demonstrates the conversion of n -butanol to aromatics (BTA) including building block aromatics over Ga modified HZSM5 catalysts in a fixed bed reactor under varying process parameters (temperature, pressure, and WHSV). Abstract : The present investigation demonstrates the conversion of n -butanol to aromatics (BTA) including building block aromatics in one step over Ga modified HZSM5 catalysts in a fixed bed reactor under varying process parameters (temperature, pressure, and weight hourly space velocity, WHSV). The several Ga modified HZSM5 catalysts prepared by the incipient wetness impregnation method were well characterized by several techniques. The different gallium species (GaO + and Ga + species) formed on Ga-HZSM5 catalysts, as confirmed by the characterization results, behave as Lewis acid sites, which played a crucial role in the enhancement of the dehydrogenation reaction and suppression of the hydride transfer reaction leading to the production of different aromatics. Specifically, the selectivity to benzene, toluene, ethylbenzene, and xylenes (BTEX) was enhanced on deposition of Ga on the HZSM5 catalyst. The selectivity to different aromatics was also affected by the variation of different process parameters. The total aromatics selectivity was raised with increasing temperature and decreasing WHSV. However, the aromatics production was reduced at high operating pressure. The high operating pressure led to the production of higher aromatics and deposition of these aromatics caused the deactivation of the catalyst. Characterization of spent catalysts confirmed the deposition of polynuclear aromatics as hard coke. The maximum total aromatics selectivity of 76.0% (BTEX 69.2%) was achieved for the 5Ga-HZSM5 catalyst at 823 K, 0.75 h −1 WHSV, and 1 atm. A comprehensive reaction pathway was recommended considering the product distribution obtained under the studied reaction conditions.